At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which pairs of expressions are equivalent, let's analyze each pair step-by-step.
### Pair A: \((\sqrt[3]{125})^9\) and \(125^{9 / 3}\)
1. Evaluate \((\sqrt[3]{125})^9\):
- \(\sqrt[3]{125}\) means finding the cube root of 125.
- The cube root of 125 is 5 because \(5^3 = 125\).
- So, \((\sqrt[3]{125})^9 = (5)^9 = 5^9\).
2. Evaluate \(125^{9 / 3}\):
- \(125^{9 / 3} = 125^3\) since \(9 / 3 = 3\).
- \(125^3 = (5^3)^3 = 5^{33} = 5^9\).
Since both expressions simplify to \(5^9\), they are equivalent.
### Pair B: \(12^{2 / 7}\) and \((\sqrt{12})^7\)
1. Evaluate \(12^{2 / 7}\):
- This expression represents 12 raised to the power of \(2 / 7\).
2. Evaluate \((\sqrt{12})^7\):
- \(\sqrt{12}\) means the square root of 12.
- The square root of 12 is \(12^{1 / 2}\).
- So, \((\sqrt{12})^7 = (12^{1 / 2})^7\).
- Using the property of exponents, \((a^b)^c = a^{bc}\), we get \((12^{1 / 2})^7 = 12^{(1 / 2) 7} = 12^{7 / 2}\).
The expressions \(12^{2 / 7}\) and \(12^{7 / 2}\) are not equivalent.
### Pair C: \(4^{1 / 5}\) and \((\sqrt{4})^5\)
1. Evaluate \(4^{1 / 5}\):
- This expression represents 4 raised to the power of \(1 / 5\).
2. Evaluate \((\sqrt{4})^5\):
- \(\sqrt{4}\) means the square root of 4.
- The square root of 4 is 2 because \(2^2 = 4\).
- So, \((\sqrt{4})^5 = (2)^5 = 2^5\).
The expressions \(4^{1 / 5}\) and \(2^5\) are not equivalent.
### Pair D: \(8^{9 / 2}\) and \((\sqrt{8})^9\)
1. Evaluate \(8^{9 / 2}\):
- This expression represents 8 raised to the power of \(9 / 2\).
2. Evaluate \((\sqrt{8})^9\):
- \(\sqrt{8}\) means the square root of 8.
- The square root of 8 is \(8^{1 / 2}\).
- So, \((\sqrt{8})^9 = (8^{1 / 2})^9\).
- Using the property of exponents, \((a^b)^c = a^{bc}\), we get \((8^{1 / 2})^9 = 8^{(1 / 2) * 9} = 8^{9 / 2}\).
Since both expressions simplify to \(8^{9 / 2}\), they are equivalent.
### Conclusion
After analyzing each pair:
- Pair A: \((\sqrt[3]{125})^9\) and \(125^{9 / 3}\) are equivalent.
- Pair B: \(12^{2 / 7}\) and \((\sqrt{12})^7\) are not equivalent.
- Pair C: \(4^{1 / 5}\) and \((\sqrt{4})^5\) are not equivalent.
- Pair D: \(8^{9 / 2}\) and \((\sqrt{8})^9\) are equivalent.
Thus, the pairs of equivalent expressions are A and D.
### Pair A: \((\sqrt[3]{125})^9\) and \(125^{9 / 3}\)
1. Evaluate \((\sqrt[3]{125})^9\):
- \(\sqrt[3]{125}\) means finding the cube root of 125.
- The cube root of 125 is 5 because \(5^3 = 125\).
- So, \((\sqrt[3]{125})^9 = (5)^9 = 5^9\).
2. Evaluate \(125^{9 / 3}\):
- \(125^{9 / 3} = 125^3\) since \(9 / 3 = 3\).
- \(125^3 = (5^3)^3 = 5^{33} = 5^9\).
Since both expressions simplify to \(5^9\), they are equivalent.
### Pair B: \(12^{2 / 7}\) and \((\sqrt{12})^7\)
1. Evaluate \(12^{2 / 7}\):
- This expression represents 12 raised to the power of \(2 / 7\).
2. Evaluate \((\sqrt{12})^7\):
- \(\sqrt{12}\) means the square root of 12.
- The square root of 12 is \(12^{1 / 2}\).
- So, \((\sqrt{12})^7 = (12^{1 / 2})^7\).
- Using the property of exponents, \((a^b)^c = a^{bc}\), we get \((12^{1 / 2})^7 = 12^{(1 / 2) 7} = 12^{7 / 2}\).
The expressions \(12^{2 / 7}\) and \(12^{7 / 2}\) are not equivalent.
### Pair C: \(4^{1 / 5}\) and \((\sqrt{4})^5\)
1. Evaluate \(4^{1 / 5}\):
- This expression represents 4 raised to the power of \(1 / 5\).
2. Evaluate \((\sqrt{4})^5\):
- \(\sqrt{4}\) means the square root of 4.
- The square root of 4 is 2 because \(2^2 = 4\).
- So, \((\sqrt{4})^5 = (2)^5 = 2^5\).
The expressions \(4^{1 / 5}\) and \(2^5\) are not equivalent.
### Pair D: \(8^{9 / 2}\) and \((\sqrt{8})^9\)
1. Evaluate \(8^{9 / 2}\):
- This expression represents 8 raised to the power of \(9 / 2\).
2. Evaluate \((\sqrt{8})^9\):
- \(\sqrt{8}\) means the square root of 8.
- The square root of 8 is \(8^{1 / 2}\).
- So, \((\sqrt{8})^9 = (8^{1 / 2})^9\).
- Using the property of exponents, \((a^b)^c = a^{bc}\), we get \((8^{1 / 2})^9 = 8^{(1 / 2) * 9} = 8^{9 / 2}\).
Since both expressions simplify to \(8^{9 / 2}\), they are equivalent.
### Conclusion
After analyzing each pair:
- Pair A: \((\sqrt[3]{125})^9\) and \(125^{9 / 3}\) are equivalent.
- Pair B: \(12^{2 / 7}\) and \((\sqrt{12})^7\) are not equivalent.
- Pair C: \(4^{1 / 5}\) and \((\sqrt{4})^5\) are not equivalent.
- Pair D: \(8^{9 / 2}\) and \((\sqrt{8})^9\) are equivalent.
Thus, the pairs of equivalent expressions are A and D.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.